2021
DOI: 10.3390/infrastructures6060083
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Vibration-Based Methods for the Prestressing Estimate in Concrete Beams with Internal Bonded or Unbonded Tendons

Abstract: The estimate of internal prestressing in concrete beams is essential for the assessment of their structural reliability. Many scholars have tackled multiple and diverse methods to estimate the measurable effects of prestressing. Among them, many experimented with dynamics-based techniques; however, these clash with the theoretical independence of the natural frequencies of the forces of internally prestressed beams. This paper examines the feasibility of a hybrid approach based on dynamic identification and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Based on the outcome of several studies, they analyzed the application of vibration-based methods for the detection of prestress losses, concluding that, in the case of uncracked beams, changes in prestress forces do not affect natural frequencies. Nowadays, research on dynamic monitoring of prestressed concrete structures remains active [22][23][24][25]. The goal of these projects is usually to verify and validate the effectiveness of vibration-based methods for damage detection.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the outcome of several studies, they analyzed the application of vibration-based methods for the detection of prestress losses, concluding that, in the case of uncracked beams, changes in prestress forces do not affect natural frequencies. Nowadays, research on dynamic monitoring of prestressed concrete structures remains active [22][23][24][25]. The goal of these projects is usually to verify and validate the effectiveness of vibration-based methods for damage detection.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the sensitivity issues of the vibration test, it is evident from the obtained results that the (pre-)stresses applied by pressing the salvaged timber elements into the voids affected the first eigenfrequency and damping ratio of the large-scale DLT elements. Whether or not the natural frequency is affected by prestressing has been discussed in some previous studies on other forms of beams made with other types of materials [34,35]. For the interpretation of the results in the study presented here, however, it should be noted that the (pre-)stresses applied here are quite different from the conventional ones.…”
Section: Vibration Characteristicsmentioning
confidence: 67%
“…This is consistent with Hamed and Frostig (2006), which concluded that the prestressing force has no significant influence on the natural frequency of prestressed concrete under nonlinear conditions. Aloisio (2021) examined the structural rigidity under the influence of prestressing force and discovered that the Young's modulus of all prestressed concrete samples showed a nearly constant elasticity at all increasing loads, thereby indicating that the rigidity was not affected by prestressing force. Furthermore, Atmaca (2019) compared the numerical natural periods of reinforced and prestressed concrete girders with identical dimensions and properties under linear and nonlinear conditions and observed that the vibrational modes of the two structures are identical.…”
Section: Introductionmentioning
confidence: 99%